FAKTOR YANG MEMPENGARUHI TINGKAT KEPUASAN PASIEN BPJS TERHADAP MUTU PELAYANAN RAWAT JALAN DI PUSKESMAS TANJUNG REJO TAHUN 2022 - Arnis, Julita; Ilham, Muhammad Aidul; Fitria, Dilla; Handayani, Sri (LPPM Universitas Awal Bros, 2025)
Background; It is important to assess patient satisfaction because it is part of service quality, is related to marketing, and is a priority for improving health services. Based on an initial survey at the Tanjung Rejo Community Health Center, it showed that 7 patients expressed dissatisfaction with outpatient services because the waiting time for services was long, the information provided by officers was incomplete and inaccurate, the poly waiting room was uncomfortable and the registration queue was quite long. Purpose; The aim of this research is to determine the factors that influence the level of BPJS patient satisfaction with the quality of outpatient services at the Tanjung Rejo Community Health Center. Method; This type of research uses a quantitative design with a cross-sectional design. The research population was all 9,430 patients with a sample of 99 people taken using the Slovin formula. Data analysis uses univariate, bivariate and multivariate analysis with logistic regression test statistics. Results; The research results show that the p value for the physical evidence variable = 0.009 < 0.05, reliability = 0.019 < 0.05, responsiveness = 0.013 < 0.05, assurance = 0.079 > 0.05 and empathy = 0.043 < 0.05, which means physical evidence, reliability, responsiveness and empathy have an influence on the quality of outpatient services, while guarantees have no influence on the quality of outpatient services. Conclusion; The research conclusion is that there is an influence of physical evidence, reliability, responsiveness and empathy on the quality of outpatient services, while guarantees have no influence on the quality of outpatient services.